THE INFLUENCE OF INQUIRY TRAINING LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN TEMPERATURE AND CALOR MATERIALS IN CLASS X OF SMA RK BINTANG TIMUR P. SIANTAR - Sri Erliani Gurning; Rahmatsyah Rahmatsyah (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
The research has been done Influence of Learning Inquiry Training Model to Student Learning Result on Temperature and Heat Material In Class X Semester II at Private High School RK Bintang Timur P.Siantar Sumatera Utara academic year 2016/2017, with the aim to know the result of student learning using Inquiry Training model and conventional learning. The type of research is quasi experiment, and sampling is done by simple random sampling. The population of this study is all students of class X. The instrument used is the test of cognitive learning outcomes and tests students' science process skills. From the data analysis for the experimental class learning results obtained the average pretest 42.00 and postest 78.20. The control class was obtained on average pretest 37,64 and postest 69,75. From the data analysis for experimental science process class skill obtained the average of pretest 36,54 and posttest 71,56. The control class was obtained on average pretest 35.02 and postest 63.89. The result of data analysis using independent sample t test shows that there is influence of instructional model of Inquiry Training on student learning outcomes on the subject matter of temperature and heat.